Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/13694332221126374
|View full text |Cite
|
Sign up to set email alerts
|

Influence lines-based model updating of suspension bridges considering boundary conditions

Abstract: The boundary conditions of the main girder are complicated for suspension bridges. And they have a significant impact on the static and dynamic response of the structure. This study proposes a model updating method based on influence lines considering boundary conditions. First, rotational and translational spring elements are used to simulate the boundary conditions of the main girder. Then, rotational spring stiffness is estimated by constructing a sensitive objective function based on the influence lines. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The FEMU method depends on the modified parameters of the model. Although some scholars have taken into account the uncertainty of these parameters [135,137,139,149] and the nonlinearity of the structure [141,142,144], in the FEM analysis of complex structures, faced with a large number of correction parameters, a repeated calculation process will lead to a slow updating process or deviation. The substructure method can decompose the whole model correction process into several independent blocks to avoid the double calculation of local damage.…”
Section: Other Femu Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FEMU method depends on the modified parameters of the model. Although some scholars have taken into account the uncertainty of these parameters [135,137,139,149] and the nonlinearity of the structure [141,142,144], in the FEM analysis of complex structures, faced with a large number of correction parameters, a repeated calculation process will lead to a slow updating process or deviation. The substructure method can decompose the whole model correction process into several independent blocks to avoid the double calculation of local damage.…”
Section: Other Femu Methodsmentioning
confidence: 99%
“…The results showed that the identified LBS had sufficient accuracy, and the analytical value of the longitudinal displacement was in good agreement with the actual value. Lin et al [137] also used a GP model to replace FEM in a study of model updating methods based on influence lines. In a case study of a long-span suspension bridge, this substitution improved the efficiency of the iterative optimization of boundary condition estimates.…”
Section: Gaussian Process-based Femumentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the temperature effect of cable suspension bridges (Lin et al, 2022; Wang et al, 2022; Xia et al, 2013; Zhou and Sun, 2019a; Zhu et al, 2022), the temperature action of cable-stayed bridges is more complicated for two reasons. First, a large number of stay cables induces high indeterminacy within the bridge.…”
Section: Introductionmentioning
confidence: 99%